ANALISIS PERBANDINGAN PRODUK UMKM JENANG MURBAROK DAN JENANG NURBAROK DI KABUPATEN KUDUS - Wardhana, Aditya (JURNAL KEBANGSAAN, 2017)
ABSTRACT Jenang as one of the products of the small and medium enterprises (SMEs) at Kabupaten Kudus in Indonesia was one of the SMEs products of Indonesia. Jenang with a brand named Mubarok and Nurbarok produced by different SMEs but having a high resemblance. The purpose of this study is to find the differences of product atributes of Jenang Mubarok dan Nurbarok from different SMEs. Research methodology used the method quantitative method with the difference analysis using Mann-Whitney U-Test with the number of population as many as 1.743.882 consumers for jenang Mubarok and as many as 577.279 from jenang Nurbarok that they came from two SMEs using nonprobability sampling technique by incidental sampling with the sample as many as 100 respondents for each. There are differences between jenang Mubarok and jenang Nurbarok on SMEs at Kabupaten Kudus Keywords : Jenang, SMEs, Mann-Whitney U-Test